The household as a driver for housing policy: is it a must? The case of the southern european countries - Santos, António Duarte (2019)
Governments are not the only actors in the area of housing policy but play decisive roles in the joint relationship of the efforts of various organizations and other entities as legalistic and formalists. It would be more important to care less about laws and more with the analysis of their social effects and impacts. The robustness of housing capital implies the existence of a massive stock of supply to avoid social risk zones. We intend to analyse how we can learn for the future with recent southern European social rationality housing policy and regulation as a strand of public policies. The consolidation of the State with regard to the organization of law and the exercise of power has given great importance to the rules of economic policy and the implementation of public policies. The sphere of housing promotion and the dual affordability of housing result from the exchange between the legislature and the executive branch.